Effectiveness of couple-based violence prevention education in reducing intimate partner violence during pregnancy in rural Ethiopia: A cluster randomized controlled trial. - Zeleke Dutamo Agde; Jeanette H Magnus; Nega Assefa; Muluemebet Abera Wordofa (PLoS ONE)
Background Pregnancy is often seen as a joyful and fulfilling time for many women. However, a significant number of women in Ethiopia experience intimate partner violence (IPV) during this period. Despite this, there is limited evidence on interventions aimed at preventing violence during pregnancy. The purpose of this trial was to examine the effectiveness of Couple-Based Violence Prevention Education (CBVPE) in reducing IPV during pregnancy in rural Ethiopia. Method A cluster randomized controlled trial was conducted using a two-arm parallel group design. The 16 clusters were randomly allocated into 8 intervention groups and 8 control groups. A total of 432 pregnant women (216 in the intervention group and 216 in the control group) participated in the trial. Couple-based violence prevention education was provided to the participants in the intervention group, while the control group received routine or standard care. We used difference-in-difference analysis and the Generalized Estimating Equation (GEE) model to assess the effectiveness of the intervention. Result At the endline, 94.9% of women in the intervention group and 95.3% of women in the control group were available for intention-to-treat analysis. There was a substantial drop in the proportion of any IPV during pregnancy from 39.4% at baseline to 13.0% at endline (p<0.001). Women in the intervention group were 74.1% less likely to report any IPV during pregnancy compared to the control group (AOR = 0.259; 95% CI 0.161-0.417). Specifically, the intervention also reduced psychological, physical, and sexual violence during pregnancy. Conclusion The study found that CBVPE is effective in reducing IPV during pregnancy in the study setting. Scale-up and adaptation to similar settings are recommended. Trial registration The trial is registered on ClinicalTrials.gov under the identifier NCT05856214 on May 4, 2023.